False-Positive Rate of a “Fourth-Generation” HIV Antigen/Antibody Combination Assay in an Area of Low HIV Prevalence - Kim, Sinyoung (American Society for Microbiology (ASM), 2010)
We retrospectively analyzed the performance of the Architect HIV antigen/antibody (Ag/Ab) combination assay in a tertiary health care center with a situation of low HIV prevalence. The specificity and positive predictive value (PPV) were 99.78% and 31.21%, respectively. However, the specificity and PPV could increase to 99.99% and 89.70% using an arbitrary cutoff value.